A study on elastic input energy based on earthquakes in Turkey - Dedeoglu, Ibrahim Ozgur; Calayir, Yusuf (Gazi Univ, Fac Engineering Architecture, 2024)
In the energy-based evaluation of structures, the effect of ground movements is taken into account through the energy input into the system. In this approach, the primary goal is to determine the input energy to the structure system. Obtaining input energy spectrums that can be used to determine this input energy in a practical way is of tremendous importance for energy-based evaluation. In this study, it is aimed to obtain the fundamental elastic input energy spectrum that can be used to determine the maximum input energy forelastic structure systems with ZC and ZD soil classes according to TBDY (2018) due to earthquake effect.For this reason, firstly, a series of strong earthquake ground motions occurring in Turkey and having data station ground classes of ZC and ZD were selected. Then, the acceleration records of these strong earthquakeground motions were scaled to have PGA values of 0,1 g. For these scaled acceleration records of each soilclass, elastic input energy spectra normalized to the mass were found and the average input energy spectrum was obtained by using these spectra. By idealizing the average input energy spectrum normalized according to the mass, a fundamental elastic input energy spectrum is proposed that can be used to practically determine the maximum energy entering the linear elastic systems for the soil class in question. The effectiveness of the proposed spectrum is examined by comparing it with the input energy spectra obtained based on the time history solutions for both soil classes.
Türkiye’de meydana gelmiş depremlere dayalı elastik giren enerji üzerine bir araştırma
Keywords: SDOF system; Elastic input energy spectrum; energy based assessment; earthquake ground motion; Turkey earthquake